Current pathophysiological concepts and management of pulmonary hypertension - Lourenço, AP (2012)
Pulmonary hypertension (PH), increasingly recognized as a major health burden, remains underdiagnosed due mainly to the unspecific symptoms. Pulmonary arterial hypertension (PAH) has been extensively investigated. Pathophysiological knowledge derives mostly from experimental models. Paradoxically, common non-PAH PH forms remain largely unexplored. Drugs targeting lung vascular tonus became available during the last two decades, notwithstanding the disease progresses in many patients. The aim of this review is to summarize recent advances in epidemiology, pathophysiology and management with particular focus on associated myocardial and systemic compromise and experimental therapeutic possibilities. PAH, currently viewed as a panvasculopathy, is due to a crosstalk between endothelial and smooth muscle cells, inflammatory activation and altered subcellular pathways. Cardiac cachexia and right ventricular compromise are fundamental determinants of PH prognosis. Combined vasodilator therapy is already mainstay for refractory cases, but drugs directed at these new pathophysiological pathways may constitute a significant advance.